Odpowiedź :
x2-4x +4-4 +y2+6y +9-9+5=0
(x-2)^2 +(y+3)^2 =8
s=(2,-3) r = pierw z 8
(x-2)^2 +(y+3)^2 =8
s=(2,-3) r = pierw z 8
x^2+y^2-4x+6y+5=0
doprowadzmay wzór do tekiej posaci aby potemmóc skorzystacz e wzoru skróconego m,nożenia
(x^2 - 4x +4) -4 + (y^2+6y +9 )-9 +5=0
(x-2)^2 + (y+3)^2= 8
środek O(2,-3)
promień pierwiastek z 8
;)
doprowadzmay wzór do tekiej posaci aby potemmóc skorzystacz e wzoru skróconego m,nożenia
(x^2 - 4x +4) -4 + (y^2+6y +9 )-9 +5=0
(x-2)^2 + (y+3)^2= 8
środek O(2,-3)
promień pierwiastek z 8
;)
x²+y²-4x+6y+5=0
(x²-4x+4)+(y²+6y+9)=8
(x-2)²+(y+3)²=(2√2)²
S=(2,-3) R=2√2
(x²-4x+4)+(y²+6y+9)=8
(x-2)²+(y+3)²=(2√2)²
S=(2,-3) R=2√2